Use of a management plan for treating asthma in an emergency department. - Town, I (1990)
A standardised management protocol has been developed for the assessment and treatment of adults with acute asthma attending an emergency department. The management protocol consists of an assessment sheet for recording essential features of the history and examination findings and a flow diagram with guidelines for initial management that were based on spirometric recordings. The protocol was introduced at Wellington Hospital in 1986. The effect of this intervention was assessed by analysing emergency department records during the three months before and one year after the introduction of the protocol. The use of the assessment sheet improved history taking and led to the increased use of serial measures of airflow obstruction and improved documentation of follow up arrangements. The provision of management guidelines influenced the emphasis of management, including an increased use of corticosteroids intravenously and more frequent use of an additional dose of nebulised bronchodilator. In the light of the initial experience the protocol has been modified and its use either in an emergency department or in general practice is recommended.